2020
DOI: 10.5018/economics-ejournal.ja.2020-5
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate volatility in the eurozone

Abstract: The current economic crisis has witnessed a strong deceleration in the growth of international trade. This has been even greater in the cases of the European Unionand the eurozone, where the rates of export growth have even reached negative figures. In this paper, the authors examine to which extent exchange rate volatility might account for the drop in the rate of growth of exports in the eurozone since the start of the crisis. To that end, they estimate export functions, augmented to include several measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Since the importance of foreign trade is not understood properly, several studies found inconclusive or conflicting conclusions when analysing the nexus between exchange rate variability and foreign trade (Auboin and Ruta, 2013). Some studies found a negative impact (Molina et al, 2013;Bahmani-Oskooee and Gelan, 2018;Sauer and Bohara, 2001) while some studies found positive association (Chi and Cheng, 2016;Bahmani-Oskooee and Saha, 2021) and few studies found no association between exchange rate variability and foreign trade (Nishimura and Hirayama, 2013;Bajo-Rubio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since the importance of foreign trade is not understood properly, several studies found inconclusive or conflicting conclusions when analysing the nexus between exchange rate variability and foreign trade (Auboin and Ruta, 2013). Some studies found a negative impact (Molina et al, 2013;Bahmani-Oskooee and Gelan, 2018;Sauer and Bohara, 2001) while some studies found positive association (Chi and Cheng, 2016;Bahmani-Oskooee and Saha, 2021) and few studies found no association between exchange rate variability and foreign trade (Nishimura and Hirayama, 2013;Bajo-Rubio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%